2006
DOI: 10.1051/0004-6361:20054635
|View full text |Cite
|
Sign up to set email alerts
|

Attempts to measure the magnetic field of the pulsating B starνEridani

Abstract: We report on attempts to measure the magnetic field of the pulsating B star ν Eridani with the Musicos spectropolarimeter attached to the 2 m telescope at the Pic du Midi, France. This object is one of the most extensively studied stars for pulsation modes, and the existence of a magnetic field was suggested from the inequality of the frequency separations of a triplet in the stars' oscillation spectrum. We show that the inferred 5−10 kG field was not present during our observations, which cover about one year… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
21
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 19 publications
6
21
0
Order By: Relevance
“…They showed that the radial velocities of the spectral lines have changed between the four sub-exposures of one polarised observation, and that such rapid changes (relative to the exposure time) in the radial velocities of the spectral lines, with an amplitude of about 7 km s −1 , create spurious signatures in the null profiles. The results of this work are consistent with a similar modelling performed by Schnerr et al (2006). In both studies we observe that the shape of the observed or modelled spurious null signatures are very similar to those of HD 156324 and HD 156424, while the amplitudes are of the same order or lower.…”
Section: Origin Of the Lsd V Signaturessupporting
confidence: 91%
“…They showed that the radial velocities of the spectral lines have changed between the four sub-exposures of one polarised observation, and that such rapid changes (relative to the exposure time) in the radial velocities of the spectral lines, with an amplitude of about 7 km s −1 , create spurious signatures in the null profiles. The results of this work are consistent with a similar modelling performed by Schnerr et al (2006). In both studies we observe that the shape of the observed or modelled spurious null signatures are very similar to those of HD 156324 and HD 156424, while the amplitudes are of the same order or lower.…”
Section: Origin Of the Lsd V Signaturessupporting
confidence: 91%
“…This step was of importance since pulsations are known to have an impact on the analysis of the presence of a magnetic field and its strength (e.g. Schnerr et al 2006;Hubrig et al 2011b).…”
Section: Spectral Variabilitymentioning
confidence: 99%
“…Since pulsations are known to have an impact on the analysis of the presence of a magnetic field and its strength (e.g. Schnerr et al 2006;Hubrig et al 2011a), as a first step, we checked that no changes in the line profile shape or radial velocity shifts are present in the obtained spectra on a short timescale of about ten minutes for HD 101412 and on a timescale of ten to 30 min for HD 190073. These timescales correspond to the exposure times of the individual subexposures during the observations of these stars.…”
Section: Magnetic Field Measurementsmentioning
confidence: 99%
“…The question of how pulsations affect the magnetic field measurements is not yet solved in spite of the fact that the number of magnetic studies of pulsating stars is gradually increasing. The effect of pulsations on magnetic field measurements was for the first time discussed by Schnerr et al (2006) and Hubrig et al (2011a). Schnerr et al (2006) discussed the influence of pulsations on the analysis of the magnetic field strength in the β Cephei star ν Eri in MUlti-SIte COntinuous Spectroscopy (MUSICOS) spectra and tried to model the signatures found in Stokes V and N spectra.…”
Section: Hd 104237mentioning
confidence: 99%
See 1 more Smart Citation